Stepwise training supports strategic second-order theory of mind in turn-taking games - Verbrugge, Rineke; Meijering, Ben; Wierda, Stefan; van Rijn, Hedderik; Taatgen, Niels (Judgment and Decision Making, 2018)
People model other people's mental states in order to understand and predict their behavior. Sometimes they model what others think about them as well: ＂He thinks that I intend to stop.＂ Such second-order theory of mind is needed to navigate some social situations, for example, to make optimal decisions in turn-taking games. Adults sometimes find this very difficult. Sometimes they make decisions that do not fit their predictions about the other player. However, the main bottleneck for decision makers is to take a second-order perspective required to make a correct opponent model. We report a methodical investigation into supporting factors that help adults do better. We presented subjects with two-player, three-turn games in which optimal decisions required second-order theory of mind (Hedden and Zhang, 2002). We applied three ＂scaffolds＂ that, theoretically, should facilitate second-order perspective-taking: 1) stepwise training, from simple one-person games to games requiring second-order theory of mind; 2) prompting subjects to predict the opponent's next decision before making their own decision; and 3) a realistic visual task representation. The performance of subjects in the eight resulting combinations shows that stepwise training, but not the other two scaffolds, improves subjects' second-order opponent models and thereby their own decisions.